"Optimizing Ad Campaigns with Machine Learning: Data-Driven Approaches in Modern Media" - Gaurav Nayyar, Sweta Suman, TR.Kalai Lakshmi (The International Journal of Multiphysics, 2024)
The rapid growth of digital platforms and the increasing consumption of media have fundamentally transformed the landscape of advertising. As traditional methods struggle to keep pace with the complexity and volume of data generated by modern audiences, machine learning (ML) offers a powerful solution to optimize advertising campaigns. This paper explores the application of machine learning techniques in ad campaign optimization, focusing on how data-driven approaches are revolutionizing media advertising. It examines various machine learning models, such as predictive analytics, natural language processing (NLP), and clustering algorithms, that enable advertisers to target audiences with precision, personalize content, and enhance engagement. By leveraging large datasets from social media platforms, search engines, and digital streaming services, machine learning models can identify patterns, predict user behaviors, and make real-time adjustments to ad placement and content delivery. This approach improves key performance indicators (KPIs), such as click-through rates (CTR), conversion rates, and return on ad spend (ROAS). Additionally, the study highlights how ML models, combined with automation, allow for dynamic pricing, better segmentation of audiences, and reduction of ad waste. The research also delves into the ethical considerations of machine learning in advertising, including concerns about data privacy and the potential for algorithmic bias. As media consumption habits evolve, the importance of machine learning in maintaining a competitive edge will only continue to grow.